THE SUEZ CANAL AS A MARITIME TRADE STRATEGIC POINT AND ITS IMPACT UPON THE ADRIATIC PORTS - Barbara Rudić; Patricija Štivičić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
This paper investigates and analyzes the strategic role of the Suez Canal in the development of international maritime trade. The development of international trade by selected years in the period from 1970 to 2021 is analyzed, in particular the state of the world merchant fleet by the ship type in recent years. Among other things, this paper examines and analysis the turnover of ships and cargoes through the Suez Canal in the last nine years. Following the basic idea, and the possibility of connecting Europe and Asia through the Suez Canal, the possibility of developing and functioning of the main logistics strategies was realized, that represent the basis for successful international trade and transport logistics of today. As part of the impact of the Suez Canal on maritime transport, special attention is paid to the impact of the Suez Canal on the ports of the northern Adriatic, which are well sheltered in the highly indented European mainland from the south and have thus ensured high competitiveness in Europe and the world. One of the main goals of this paper is to emphasize the fact that the Suez Canal and the gravitational hinterland of the northern Adriatic ports with their land traffic routes are the key elements in determining the development and operation of the northern Adriatic ports.